REALITAS PELACURAN PEMANDU LAGU - Wa Ode Nurul Yani (Dialektika, 2019)
The rise of Song Guidance (PL) services in karaoke centers in the city of Bandung as a result of the complexity of human needs, while the available work area is limited, resulting in some people taking shortcuts to get money in fulfilling their daily needs. Song Guides as covert prostitution are one easy job choice for someone who is not skilled and has a low education, but with the hope of getting a decent life by undergoing the profession as a prostitute who conducts sex transactions at karaoke venues. Difficulties in life that affect PL mental or moral conditions in fulfilling life's needs, even though the work done is contrary to morality, morality and religion, many women who live in poverty become prostitutes only to obtain food, clothing and protection, the reason they take the road shortcut is to get money to meet their needs and family. The doctrine of sin for prostitutes must be removed and instead sympathy and affection for the prostitutes must be given.